2010
DOI: 10.1111/j.1556-4029.2009.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive “Water Test”—An External Indicator of Base of Skull Hinge‐Ring Fracture

Abstract: Despite having significant internal injuries, victims of motor vehicle accidents may have surprisingly few external manifestations of trauma. The water test describes a technique whereby water placed in an upwardly facing ear results in drainage from the nose and opposite ear, thus demonstrating transcranial passage of water. This sign can be demonstrated in cases of blunt cranial trauma where there is a "hinge" fracture involving the petrous temporal bones bilaterally associated with a ring fracture extending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…The causes of death in cases of ring fracture include dislocation of the atlantooccipital junction, pontine hemorrhage, brainstem injury and vascular injuries 2) . Although sudden heart arrest caused by brain stem injury represents a leading cause of death in the field 1 , 8) , this condition remained unfamiliar to forensic doctors until recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of death in cases of ring fracture include dislocation of the atlantooccipital junction, pontine hemorrhage, brainstem injury and vascular injuries 2) . Although sudden heart arrest caused by brain stem injury represents a leading cause of death in the field 1 , 8) , this condition remained unfamiliar to forensic doctors until recently.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of chin impact, the presence of a mandible fracture reduces the incidence of the pontomedullar laceration by 2.3-fold compared to the absence of such a fracture 12) . In addition, ring fractures can also be accompanied by cerebrospinal fluid rhinorrhea and/or otorrhea 1) .…”
Section: Discussionmentioning
confidence: 99%
“…Deformed laminae are called hinges. 14,15 Deformed lamina fractures, also called hinge fractures, could occur intraoperatively during creation of a hinge and can occur postoperatively during the recovery stage. 16 Sometime a hinge fracture occurs regardless of the proper hinge angle.…”
Section: Introductionmentioning
confidence: 99%
“… 2 9) The basic principle of laminoplasty have included linear laminectomy on one side and making greenstick deformation of opposite side laminas. 1 9) These deformed laminas were called as hinges. The initial technique for laminoplasty had some problem such as lamina reclosure or hinge fractures (HFs).…”
Section: Introductionmentioning
confidence: 99%
“… 5 7) Nevertheless, HFs had been reported. 1 5) Some authors had been reported that HFs might be related with chronic neck pain or palsy, and had analyzed risk factors associated with HFs. 3 5 6) However, there was few studies about surgical techniques related with HFs.…”
Section: Introductionmentioning
confidence: 99%